Scales and power in river basin management: the Chao Phraya River in Thailand - Molle, Francois (2007)
Interventions on hydro/ecological systems by different categories of stakeholders characterised by different political, decision-making and discursive power, and varied access to resources, tend to generate costs, benefits and risks that are distributed unevenly across spatial and temporal scales and across social groups. This is due to the interconnectedness of users through the hydrologic cycle entailed by their dependence upon the same resource. As pressure over resources increases and basins 'close', this interdependence becomes more critical, increasing the frequency and seriousness of water shortages and conflicts. A political ecology approach seeks to identify and understand the mechanisms that underpin the transformations of aquatic socioenvironmental systems. Basin interconnectedness, with its hydrological, ecological and social dimensions, and three instances of the concept of scale are shown to be relevant to the understanding of these transformations. The paper analyses the case of the Chao Phraya river basin, in Thailand, and shows how land and water resources have been appropriated and identifies the different interest groups and their related discourses and power; it examines how they have adapted to socio- environmental changes, and highlights how risks, costs and benefits have been distributed.